Pendidikan Gizi Berpengaruh Terhadap Pengetahuan dan Sikap Mengenai Gizi Seimbang pada Remaja Putri Kurang Energi Kronik di Madrasah Aliyah Negeri 2 Banjar - Norhasanah Norhasanah; Atika Puspa Dewi (Jurnal Kesehatan Indonesia, 2021)
Adolescent health is essential to note because healthy teenagers will be able to produce high-quality future generations for the nation. One of the efforts to improve health can be performed by improving knowledge and positive attitudes towards health. This study aimed to analyze the effect of nutrition education on knowledge and attitudes about balanced nutrition in adolescent girls with chronic energy deficiency. This study used a pre-experimental design with a one-group pretest and posttest approach. The study population was 149 adolescent girls aged 15 years in 10th and 11th grade of Islamic Senior High School 2 Banjar, and the sample was 33 adolescent girls. The data regarding knowledge and attitude about balanced nutrition were collected through interviews using a structured questionnaire. Differences in knowledge and attitudes about balanced nutrition in adolescent girls before and after nutrition education interventions were analyzed using the Wilcoxon test. The results showed that the average score of balanced nutrition knowledge in adolescent girls before the nutrition education intervention was 48.80±11.7, which increased to 89.15±8.5 after the intervention (p-value=0.000). The average score of balanced nutrition knowledge in adolescent girls before the intervention was 82.44±4.3, which increased to 87.05±4.2 after nutrition education (p-value=0.000). These results indicated that nutrition education could increase the knowledge and attitudes about balanced nutrition in adolescent girls.